Periphrases in media headlines - Bulakh , Maiia (Current issues of Ukrainian linguistics: theory and practice, 2018)
The stylistic potential of periphrases in the headlines of media texts is analyzed. The relevance of the stated topic is due to the important role of the headline in media texts, its polyfunctional nature. The main functions of the headline, in particular: nominative, informative, expressive, advertising, manipulative – correspond to the basic functions of the media (information and influence on the audience). In accordance with these functions, the headline actualizes the expressive and evaluative features of the language, one of which is the periphrasis. Periphrastic constructions in the headlines reinforce the semantic coherence of the text, a positive or negative assessment, and emotion. The factual material illustrates the use of allusion periphrasis that creates secondary contextual nominations, and conveys the basic meaning of information in an expressive periphrastic form. The meaning of such transformed periphrastic constructions is revealed in the structure of the text, thereby attracting the recipient and encouraging him to read the media material. As the factual material shows, in the structure of media headlines, as a rule, the well-known periphrases are used with a special cultural connotation fixed in the consciousness of the society. It is also noted that transformed periphrases often represent an allusion to known cultural phenomena (historical events, the names of movies, fiction). In the work, it is noted that the periphrastic constructions, replacing the same denotation in the headline, subtitle, and main text, create an additional semantic coherence of the text. The analysis made it possible to determine that the periphrasis in the header of the media text also combines the structural components of the title and paragraphs, affects the architectonics of the entire media text, accumulating information important for the perception of the text. The study allows us to conclude that the periphrasis in the headline structure affects the emotive and logical levels of perception. On the basis of illustrations, it is shown that periphrases in headings are an effective tool for achieving the main goal of media texts – the impact on the recipient.